Navigating through the ebbs and flows of language. (October 2021) - Viol, Aline; Treves, Alessandro; Ciaramelli, Elisa
Abstract: Is progress in understanding the neural basis for spatial navigation relevant to the human language faculty? Not so much at the shortest scale, where movement is continuous, a recent study in the space of vowels suggests. At a much larger scale, however, that of the verbalization of run-away thoughts, a rich phenomenology appears to involve critical contributions by some of the brain structures also involved in spatial cognition. Their interactions may have to be approached with models operating at an integrated cortical level and allowing for the compositionality of multiple local attractor states. A useful window on the latching dynamics enabled by cortico-cortical interactions may be offered by altered states of consciousness. As an example, psychedelic states have been reported to alter the graph properties of functional connectivity in the cortex so as to facilitate wide-ranging trips.